Restaurant finding mobile application / Muhammad Aidy Hafizee Mohyeden - Mohyeden, Muhammad Aidy Hafizee (2020)
Restaurant Finding is a mobile application that has been developed to help user in finding restaurants and as a medium for restaurant owner to promote their restaurant. Based on survey that has been made, there are several problems faced by customer in finding restaurant such as do not know the location of the restaurant , what kind of the cuisine that the restaurant have and for the restaurant owner, they do not have a specific platform to promote their restaurant. This project is carried out with an aim to develop Restaurant Finding Mobile Application using the methodology Mobile Application Development Lifecycle (MADLC) that consist of six (6) phases which are identification, design, development, prototyping, testing and maintenance. However, only three (3) phases are used in these projects to achieved objectives which are used in this project to achieved objectives which are identification, design and development. Each phase contents several activities to be finished in order to achieve objectives. As a result, the application is developed together with documentation of Software Requirement Specification (SRS) and Software Design Document (SDD). The challenges faced during running this project includes skills and experience and understanding project plan. In the future work, this system might need additional of new features such as it will compatible with iOS platform. Include GPS for navigate the location and also booking features for customer.